2021
DOI: 10.3389/fcell.2021.595744
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Conserved Shh Enhancer Coordinates Hypothalamic and Craniofacial Development

Abstract: Enhancers that are conserved deep in evolutionary time regulate characteristics held in common across taxonomic classes. Here, deletion of the highly conserved Shh enhancer SBE2 (Shh brain enhancer 2) in mouse markedly reduced Shh expression within the embryonic brain specifically in the rostral diencephalon; however, no abnormal anatomical phenotype was observed. Secondary enhancer activity was subsequently identified which likely mediates low levels of expression. In contrast, when crossing the SBE2 deletion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
(60 reference statements)
2
3
0
Order By: Relevance
“…1 C). These defects are consistent with SHH deficiency at early neurulation, as seen in Shh mutant mouse embryos ( Carreno et al, 2017 ; Corman et al, 2018 ; Crane-Smith et al, 2021 ; Szabo et al, 2009 ). However, contrary to prior analysis that focused on developmental stages after E9.5, our data uncovered that GAS1 is not required for initial establishment of the SHH domain in the RDVM at E8.5, but is necessary to sustain its activity at later stages of neurulation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…1 C). These defects are consistent with SHH deficiency at early neurulation, as seen in Shh mutant mouse embryos ( Carreno et al, 2017 ; Corman et al, 2018 ; Crane-Smith et al, 2021 ; Szabo et al, 2009 ). However, contrary to prior analysis that focused on developmental stages after E9.5, our data uncovered that GAS1 is not required for initial establishment of the SHH domain in the RDVM at E8.5, but is necessary to sustain its activity at later stages of neurulation.…”
Section: Discussionsupporting
confidence: 82%
“…S2 " type="url"/> ). These changes recapitulated phenotypes seen in Shh mutant mice ( Carreno et al, 2017 ; Corman et al, 2018 ; Crane-Smith et al, 2021 ; Szabo et al, 2009 ) and further substantiated a role for GAS1 in control of SHH activity in the developing forebrain neuroepithelium.
Fig.
…”
Section: Resultssupporting
confidence: 61%
“…Phenotype associated with Shh inactivation varied based on the mouse strain, with C57BL/6J background showing a more pronounced effect (Lo et al, 2021). development (Carreno et al, 2017;Crane-Smith et al, 2021;Hamdi-Rozé et al, 2020;Zhao et al, 2012). Recent research also found that mice heterozygous for Six3 displayed a similar pituitary-restricted phenotype due to Six3's control of Shh in the ventral forebrain (Bando et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This developmental anomaly arises from the abnormal persistence of the tissue connecting Rathke's pouch to the oral ectoderm during development. Studies on conditional knockout mice revealed the crucial role of Shh in the ventral diencephalon for Rathke's pouch development (Carreno et al, 2017 ; Crane‐Smith et al, 2021 ; Hamdi‐Rozé et al, 2020 ; Zhao et al, 2012 ). Recent research also found that mice heterozygous for Six3 displayed a similar pituitary‐restricted phenotype due to Six3's control of Shh in the ventral forebrain (Bando et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation